Pemaknaan Hadis-Hadis Jihad dalam Website VOA ISLAM dan Relevansinya dengan Diskursus Islam Indonesia - Wasoni, Wasoni; Helmy, Muhammad Irfan (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
The Meaning of the Hadiths of Jihad in the VOA ISLAM Website and its Relevance to Indonesian Islamic Discourse This paper aims to determine the meaning of jihad hadiths on website and their relevance to Indonesian Islamic discourse. This is based on the phenomenon in which the current era of jihad hadith is often interpreted textually because it only relies on an understanding that is physical or literal. While the actual understanding of hadith is not that simple, it involves checking the sanad (transmission of hadith) and matan. If sanad and matan of a hadith are considered authentic, the next step is the use of fiqh al-hadith as a method for understanding a hadith by involving the socio-historical side and contextualizing meaning. Today, websites often used as references as legal references or solutions to various problems of Muslims. One of them is website which contains a lot of Islamic discourse that contains hadith, one of which is the hadith about jihad. This research is a qualitative research in the form of library research with descriptive analysis method. The meaning applied by website in understanding jihad hadiths is textually (haqiqi), that the word jihad in the hadith is understood more about war. The relevance of the meaning of jihad hadiths on website , especially on the meaning of war jihad, is irrelevant to Indonesian Islam. This is based on the situation and conditions of religious and state life in Indonesia which upholds peace. Moreover, the identity of Indonesian Islam is Islam wasathiyah (moderate), which leans on the principles of tawasuth, tawazun, ta'adul and tasamuh which cover various aspects of life.